Black ice - Giarratano, Leah (Sydney ; New York : Bantam, 2010)
"Beautiful people can do terrible things . . . A mother out of gaol, hell bent on vengeance, desperate to be reunited wiht her son. An ambitious cop trying to bust a Sydney drug cartel. A glamorous society couple living the high life - he's a successful lawyer, she's a model. He's also feeding her growing cocaine and ice habit. When Detective Sergeant Jill Jackson goes undercover to investigate Sydney's drug lords, these worlds collide. Soon people are going to get hurt."--Website.
First published by Bantam in 2009.
Imprint: RHA eBooks Adult.
Audience: General.
Description based on print version record
Keywords: Drug abuse and crime -- New South Wales -- Sydney -- Fiction; Policewomen -- Australia -- Sydney (N.S.W.) -- Fiction; Policewomen -- New South Wales -- Sydney -- Fiction; Crime & mystery; Fiction - Mystery & Detective - General; Policewomen; New South Wales -- Sydney; Australian; Electronic books; Fiction